Systematics of landscape architecture objects in the modern city - Kłopotowski, Maciej (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
For decades there has been an ongoing work aimed at systematizing landscape architecture objects and keeping their classification. The author in his research also takes up this subject and conducts his work on the background of historical circumstances, including knowledge and practice of design. Unlike with the previous measures, the author here adopts area planning as the base (starting point) of works systematizing problems of theory. The subsequent (two-stage) greenery divisions are completed by the assignment of specific objects of landscape architecture. Subsequently they are juxtaposed with the determinants of localization, specifying their location in a particular town zone.